Disputes and resemblance: comparative analysis of shariah advisory committee methodology and International indices / Wan Arliza Wan Zainal … [et al.] - Wan Zainal, Wan Arliza; Kasim, Nawal; Zakaria, Nor Balkish; Mohamed, Norazida (Universiti Teknologi MARA Cawangan Selangor, 2016)
In line with Malaysian Capital Market Masterplan 2 to expand the Islamic capital, Malaysian Shariah Advisory Council (SAC) has revised the Shariah screening process for listed companies in late 2013. The screening methodology was revised by adopting a two-tier approach to the quantitative assessment which applies business activity benchmarks and newlyintroduced financial ratio benchmarks while maintaining the qualitative assessment at the same time. This revision is parallel with the international screening providers (such as Dow-Jones Islamic World Market, Morgan-Stanly Compliance Islamic Index, London Stock Exchange (FTSE) Shariah Index, and Standard and Poor Shariah Index) methodology to identify Shariah-compliant investment for Muslims investors. Despite the similarity between the latest SAC 2013 Shariah screening methodology and the International Indices, various discussions on these screening methodology implications and detail filters are still being debated. The questions on which indices best follow the Shariah rules and are too liberal have yet to be discovered. Thus, there could be a need to provide clearer understanding with a more uniform Shariah investment screening methodology to convince investors with international portfolios. Any disputes or resemblance among these international indices and SAC are highlighted in this paper.